Pembatasan Oligarki dalam Mewujudkan Sistem Demokrasi di Indonesia - Ghiyats Amri Wibowo; Muhammad Alfin Imanullah; Haqie Religia Saintika; Fayza Reizha Isfany (Universitas Muhammadiyah Yogyakarta, 2024)
The widening economic gap and the domination of wealth by a small number of individuals in Indonesia highlight key challenges in realizing an inclusive and equitable democracy. Popular sovereignty reflects democracy, which represents the majority's voice. However, in reality, the people's voice is degraded by the voice of the oligarchs who own the majority of wealth in Indonesia. This research explores economic oligarchy's implications on the Indonesian democratic system. The used is juridical-normative legal research or also called document research with secondary data as the main source. Researchers conduct legislative studies to see synchronization between legislation. Data were collected using literature review techniques, such as perusing, analyzing, and drawing conclusions from relevant documents. The research results confirm that the dominance of oligarchs grows and develops due to the high political costs of elections, so power relations are formed between the rulers and the oligarchs. As a result, oligarchs become regulators and executors in the state administration system, which has implications for the difficulty of achieving the ideals of a more inclusive democracy. Therefore, to limit oligarchy, policy reform is needed that is more oriented towards social justice, economic equality, and meaningful participation in realizing checks and balances